THE EXPERIENCES OF THE INTERNATIONAL INSTITUTE OF ISLAMIC CIVILISATION & MALAY WORLD (ISTAC), INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA IN EMPOWERING THE MALAY WORLD & ISLAMIC CIVILISATION - Zakariya, Hafiz; Yadi, Suryadi (Center for Research and Development of Religious Literature and Heritage, 2017)
Although Indonesia and Malaysia are now two independent nations, both countries have a lot in common, tied by a common religion, language and cultural heritage dating back centuries ago. In building a better tomorrow, both nations can benefit from each other’s rich experiences. This paper will focus on an educational institute established at the International Islamic University (henceforth, IIUM) in 2016 initially named the Centre for Malay World and Islamic Civilization and now has been transformed as the International Institute of Islamic Civilization & Malay World (henceforth, ISTAC). The institute is established to support the efforts of the university in creating an academic and intellectual field of research and studies focusing on the Malay World and Islamic civilization. This study describes the scope, major types of activities and concerns of the institute. In so doing it will identify the potential areas for collaboration (such as academic exchange, research, international conference) with relevant institutions in Indonesia.